A mechanically robust transparent coating for anti-icing and self-cleaning applications - Wu, Xinghua (2019)
Mechanically robust, transparent coatings that display very low affinity with ice and various liquids are promising for applications in outdoor facilities and marine and aerospace structures. However, such coatings are extremely challenging to prepare because some material properties required for diverse functionalities are contradictory. In this study, we demonstrated a sol-gel-derived transparent coating with superior performance compared to the well-studied superhydrophobic coatings in terms of transmittance (∼97.8%), ice-adhesion strength, anti-frost accumulation, and self-cleaning properties. We comprehensively investigated the mechanical properties of the transparent solid coating by nano-indentation, pencil scratch, cross-cut adhesion, and dolly pull-off tests according to the respective ASTM/ISO standards. The coating displayed higher hardness and better scratch resistance than the state-of-the-art slippery liquid-infused porous surfaces and polymer coatings. Furthermore, the coating showed good durability after sand erosion.